Konstrukcja słupowa na majdanie grodziska ze starszych faz wczesnego średniowiecza w Dakowach Mokrych, pow. nowotomyski. Rozważania dotyczące tzw. budynków halowych - Jagoda Mizerka (Slavia Antiqua)
In the mid-1970s, a probing excavation was carried out on a hillfort at Dakowy Mokre in south-western Wielkopolska, dated by traditional and naturalistic methods to the older phases of the early Middle Ages. The results of this excavation have not yet been compiled and published. The article deals with the discovery of at least 16 post holes in the central part of stronghold, in some kind of arrangement, over an area of more than 60 m2. In the disputed part, two possible hypotheses are considered, i.e. interpreting the arrangement of the pits as the remains of a residential/farming building or as a pseudo-hall object, referring in its idea to the hall buildings recognised in Western Europe. For both, known analogies from Polish, German and Bohemian lands were collected and updated with the latest discoveries. As not a sufficient surface has been exposed, this text does not conclusively determine the nature and function of the post construction, but it does provide new information on the development of late-tribal hillfort settlements, and thus the functions they performed.